Understanding metapsychology with the computer paradigm - Hartmann Cardelle, Volker; Dietrich, Dietmar (Metapsychologica - rivista di psicanalisi freudiana, 2022)
In this article we want to assail the task of providing an answer to the much-disputed question whether psychoanalysis is, as Freud claimed, a natural science or not. We want to argue in favour of Freud’s view, but at the same time break out of the polarization that emerged around the assumption that the only way to develop a natural scientific approach to the human mind is the neuroscientific approach. We will do so by explaining the basis of our understanding of metapsychology: the computer paradigm and why it is not only a valid natural scientific paradigm but also in line with Freud’s thinking. Based on this paradigm we shall provide an explanation of how we interpret the concept of the mental apparatus and why it is that metapsychology is the only psychological theory that allows for experimental testing and refinement. We will illustrate our understanding of metapsychology by providing an interpretation of Freud’s Project for a Scientific Psychology that tries to overcome the usual polarization in the discussions of this text. The core thesis of this interpretation is that the Project cannot be seen as a metapsychological text.